Metode Mnemonic dalam Pembelajaran Menulis Aksara Jawa - Sutriono Hariadi (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2021)
Learning local languages (Java) for SMP student is not always a filed of study that is easily accepted and inderstood. Java language study material that is difficult for students to master one is writing with Java script. The things that make student difficult writing Java script is a form letter, distinguishing letters, and put the letter. Therefore, measures to overcome the difficulties of the student is to find a method of learning to write Java script quickly and easily. Mnemonic method is a strategy or techniques that are studied to help the performance of memory. Mnemonic methods has a wide variety of techniques. In the learning to write Java script, techniques that can be used is the technique of imajery visual and technical categories. The technique is a techniques based on the grouping of categories, where as the technique is of imajery visual is a technique to imagine other objects.